Utilização de arte conceitual para geração de modelos 3D - Renato Dias Viana (2014)
This document presents a set of tools that automates the creation of 3D models from conceptual sketches. The traditional approach to 3D model creation consists of an artist developing conceptual art of the objects, and later, a 3D modeller creates the model manually based upon these sketches, using software such as Maya, Bleder or 3D Studio Max. This is a slow and costly process. It was developed an application that receives as input the images of the concept art and outputs the 3D models. The application uses techniques derived from the Visual Hull and the Marching Intersections algorithms. Results proved that the application is capable of generating acurate models for several, very simplified sketches.